The Treatment of Severe Congenital Scoliosis Associated With Type I Split Cord Malformation: Is a Preliminary Bony Septum Resection Always Necessary?. Issue 2 (27th July 2018) - Huang, Zifang; Li, Xueshi; Deng, Yaolong; Sui, Wenyuan; Fan, Hengwei; Yang, Jingfan; Yang, Junlin
Abstract: BACKGROUND: Single-stage spine-shortening osteotomy without treating spinal cord malformations may have potential advantages for the treatment of severe congenital scoliosis (CS) with type I split spinal cord malformation (SSCM); however, the study of this technique was limited. OBJECTIVE: To evaluate the safety and efficacy of a single-stage spine-shortening osteotomy in the treatment of severe CS associated with type I SSCM. METHODS: A retrospective study was designed to compare 2 case series including 12 severe CS patients with type I SSCM and 26 patients with type A cord function (without spinal cord malformations, evoked potential abnormalities, and neurological dysfunctions preoperatively) treated with a single-stage spine-shortening posterior vertebral column resection (PVCR). Patient demographic, clinical, operative, and radiographic data were obtained and compared between groups. RESULTS: The surgical procedure was successfully performed in both groups, and the patients were observed for an average of 44.9 mo (range 25-78 mo) after the initial surgery. The radiographic parameters, intraoperative data, and new neurological deficits showed no difference, while deformity angular ratio (SSCM group: control group = 16.6 ± 3.6: 20.1 ± 3.9, P = .01) and corrective rate (SSCM group: control group = 50%: 58%, P = .046) of the main curve were statistically different between groups. All of the new neurological deficits were recovered within 1 yr. CONCLUSION: The single-stage spine-shortening PVCR with moderate correction could be applied to the treatment of CS associated with type I SSCM. This strategy can achieve safe spinal deformity correction while obviate the neurological complications brought by the detethering procedures, which merits further clinical investigation.